2016
DOI: 10.1371/journal.pone.0152823
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-Band Ultraviolet B Phototherapy Ameliorates Acute Graft-Versus-Host Disease of the Intestine by Expansion of Regulatory T Cells

Abstract: Narrowband ultraviolet B (NB-UVB) has been widely used in dermatological phototherapy. As for the application of NB-UVB phototherapy to graft-versus-host disease (GVHD), we previously reported that it was highly efficacious for cutaneous lesions of acute GVHD (aGVHD) and that expansion of regulatory T (Treg) cells induced by NB-UVB might be one of the mechanisms. In order to examine whether NB-UVB irradiation through expansion of Treg cells is effective for the treatment of not only cutaneous aGVHD but also aG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…UVB‐induced regulatory T cells have been widely considered to mediate UVB‐induced immunosuppression by inhibiting T effector cells (). However, because of the lack of regulatory T cell depletion experiments in our study, we cannot exclude a suppressive role of regulatory T cells in our research model.…”
Section: Discussionmentioning
confidence: 99%
“…UVB‐induced regulatory T cells have been widely considered to mediate UVB‐induced immunosuppression by inhibiting T effector cells (). However, because of the lack of regulatory T cell depletion experiments in our study, we cannot exclude a suppressive role of regulatory T cells in our research model.…”
Section: Discussionmentioning
confidence: 99%
“…In mastocytosis, phototherapy might act by direct cytotoxicity against activated mast cells and by stabilizing mast cells, thus inhibiting them from releasing soluble proinflammatory mediators such as histamine ( 89 ). In graft vs. host disease (GVHD), the predominant mechanism of action may be immunomodulation by downregulating the activity of grafted cells against the host ( 90 ). The effect of OVB in pruritus remains entirely elusive at the moment; however, a halfside comparison study implied a systemic effect, since treatment reduced pruritus not only on the irradiated body half but also to an equal degree on the unirradiated side ( 91 ).…”
Section: How Does Phototherapy Work?mentioning
confidence: 99%
“…[14,19] Iyama et al showed that NB-UVB treatment expanded CD4 + CD25 + Foxp3 + regulatory T cells in peripheral blood of patients with cutaneous aGVHD, and NB-UVB-induced regulatory T cells may be functional in the skin and intestine or liver, based on a mouse model of aGVHD. [20] It is unknown if a systemic increase of regulatory T cells impairs the GVT effect and increases the risk for relapse, [11] which emphasizes the need to be cautious about relapse of underlying hematologic malignancy. In addition, use of NB-UVB has occasionally been associated with emergence of cutaneous cancers, especially in immunocompromised patients, and GVHD itself may increase the risk of melanoma and nonmelanoma skin cancer.…”
Section: Discussionmentioning
confidence: 99%